Peran Badan Pertanahan Nasional dalam Menangani Konflik, Sengketa dan Perkara Pertanahan di Kota Semarang - Jimny Suryo Pamungkas; Purwoko .; Pudji Astuti (Journal of Politic and Government Studies, 2016)
Semarang as the capital of central java is one of big cities in indonesiawith a population of as many as 1.765.396 lives in 2015 area 373.67 km2 andthe more rapidly with the emergence of housing only , apartment , restaurantand hotel .The state of do not possible that would be triggered dispute andconflict land within the city of semarang .In 2010 legal aid institute ( LBH )noted be more than 10 thousand hectares land in central java contested.Covering land was split in 46 cases land dispute. In comparison further ,2009 there are 42 land conflicts with broad 10.587,18 hectares. While datafrom a consortium of agrarian reform ( KPA ) central java show , along thisyear there are 163 conflict of agrarian affairs in the city of semarang with thenumber of people or farmers who became the victims were killed by a bombthis conflict reached 22 people .From the data kpa , agrarian conflict thathappened in the year 2011 involving 69.975 heads of household by the area ofthe space conflict reached 472.04 hectares .Of 163 conflict of agrarian affairsin 2010 , the details are 97 cases in the plantation sector , 36 cases in theforestry sector , 21 cases in the infrastructure sector , 8 cases in the miningsector , and 1 case in the region of fish-ponds or coastal and it is notimpossible that will increase again if not addressed .The purpose of this study is to find the role and strategies nationalland agency ( BPN ) the city of semarang as one of government agency in adispute case , conflict and matter land .The data collected directly from theor source that deals with this research , obtained through direct interviewwith respondents .The interviews conducted by determining key person.Informants selected can provide informants relevant to this research is2pertaining to role of government in a dispute case of land the city ofsemarang the national land agency ( BPN ) the city of semarang.Based on the research done the role of bpn in a dispute case of land itcan be seen that they are implement accordance with the procedure that is.Can be seen from the way they resolve the case of between siti part withn.v.bow & amp; cultuur mastechappij karangaju now changed its name intopt .Construction company and plantation karangayu .The strategy took bybpn the city of semarang effective over the result of startegi it is there are thenumber of cases from year 2012-2014 there are 1039 a disputed case land inthe city of semarang .Of 1039 a disputed case land in the city of semarang ,that were settled by bpn the city of semarang as many as 646 a case or 62 %.Keywords: role , strategy , land conflict